Do financing models in Islamic bank affect profitability? Evidence from Indonesia and Malaysia - Multazam Mansyur Addury (Journal of Islamic Economics Lariba, 2023)
IntroductionPrevious literature discussed financing's impact on performance without separating the financing model. Additionally, previous research has used financing in the form of Loans to Total Assets (LTA); a proxy used to assess bank liquidity.ObjectivesThis study aims to analyze the influence of financing models on Islamic Banks’ performance in Indonesia and Malaysia. MethodThe study used Indonesia and Malaysia banks for its pioneering efforts in establishing Islamic banking in Southeast Asia. The study collects data from five Indonesian and four Malaysian Islamic banks, with an observation period of 2011–2020. The data analysis used in this study was the Generalized Method of Moment (GMM).ResultsIn Indonesia, debt financing has a positive and significant impact on Return on Assets (ROA), while equity financing has a negative and significant impact on ROA; debt financing significantly affects Return on Equity (ROE), while equity financing does not have a significant impact on ROE. In Malaysia, equity financing has a positive and significant impact on ROA, while debt financing does not significantly affect ROA; debt financing has a positive and significant impact on ROE, while equity financing has a negative and significant influence on ROE. ImplicationsThe results highlight the importance of considering the specific characteristics of each country's Islamic banking industry when formulating financing strategies.Originality/NoveltyThis study highlights unique aspect of financing that contribute to Islamic banks profitability in Indonesia and Malaysia.